Determination of Trace Metal (Mn, Fe, Ni, Cu, Zn, Co, Cd and Pb) Concentrations in Seawater Using Single Quadrupole ICP-MS: A Comparison between Offline and Online Preconcentration Setups - Saumik Samanta (MDPI AG, 2021)
The quantification of dissolved metals in seawater requires pre-treatment before the measurement can be done, posing a risk of contamination, and requiring a time-consuming procedure. Despite the development of automated preconcentration units and sophisticated instruments, the entire process often introduces inaccuracies in quantification, especially for low-metal seawaters. This study presents a robust method for measuring dissolved metals from seawater accurately and precisely using a seaFAST and quadrupole Inductively Coupled Plasma Mass Spectrometer (ICPMS), employed in both offline (2016–2018) and online (2020–2021) setups. The proposed method shows data processing, including the re-calculation of metals after eliminating the instrumental signals caused by polyatomic interferences. Here, we report the blank concentration of Fe below 0.02 nmol kg−1, somewhat lower values than that have been previously reported using high-resolution and triple-quad ICPMS. The method allows for the accurate determination of Cd and Fe concentrations in low-metal seawaters, such as GEOTRACES GSP, using a cost-effective quadrupole ICPMS (Cdconsensus: 2 ± 2 pmol kg−1, Cdmeasured: 0.99 ± 0.35 pmol kg−1; Feconsensus: 0.16 ± 0.05 nmol kg−1, Femeasured: 0.21 ± 0.03 nmol kg−1). Between two setups, online yields marginally lower blank values for metals based on short-term analysis. However, the limit of detection is comparable between the two, supporting optimal instrumental sensitivity of the ICPMS over 4+ years of analysis.